El lenguaje oral y las técnicas didácticas infantiles. - Quishpe Álvarez, Pamela Margoth (2018)
The present project was based on the importance of the Infantile Didactic Techniques in the development of the Oral Language in the children of 5 to 6 years of the Dr. Ricardo Cornejo Rosales Educational Unit of the Guamaní parish, in the city of Quito, in the period 2017-2018. The problem posed by the research was to know how children's didactic techniques influenced the development of oral language. The objective of the research was to determine the development of oral language through the application of didactic techniques in children in the first year of basic general education of the Educational Unit "Dr. Ricardo Cornejo Rosales. In relation to the theoretical framework of this research was based on the theories of psychological, pedagogical and educational learning, it was resorted to obtain information from primary and secondary sources, the level of research is descriptive. This research work was feasible through an interview conducted with the DECE (Department of Student Counseling), a survey of teachers and parents that could be represented through tables and graphs, and important information was obtained from it that was analyzed and interpreted. Finally it expresses the conclusions and recommendations of the research, the suggestions to improve and extend the research and overcome the problems to the students, culminated with the bibliography. In annexes, the instruments used in the investigation, the evidences and validated documents are attached.